Development options for Africa in the 1980s and beyond - Ndegwa, Philip; Mureithi, Leopold P.; Green, Reginald Herbold; Society for International Development (Nairobi : Oxford University Press in association with the Society for International Development, Kenya Chapter, 1985)
These are papers presented at the Symposium on Development Options for Africa in the 1980s and Beyond, organized by the Kenya Chapter of the Society for International Development, held at the Kenyatta Conference Centre, Nairobi, Mar. 7-9, 1983.
Includes bibliographies and index.
hza 28/01/2019
Loans
Keywords: Development economics; Africa